Esthetic Replacement of Missing Antetior Tooth with All Ceramic Restoration (IPS E.max Cad) – A Case Report - Praveen P1 , Ragavendra Jayesh2 , Sanjna Nayar3 . (Indian Journal of Forensic Medicine & Toxicology, 2020)
In Dentistry, ceramic restoration has become more popular among other dental restorative material, becauseof its superior esthetics, good biocompatibility as well as excellent mechanical and physical properties.Among dental ceramics -Lithium Disilicate (LD) glass ceramics and Polycrystalline Zirconium DioxideCeramics are used as a dental biomaterial and also the material of choice for esthetic replacement ofmissing anterior teeth.These materials exhibit better esthetics, color stability, biocompatibility as well asbetter strength. Theyact as a most promising restorative materials because it has favourable mechanical andphysical properties compared to other restorative materials.